USE OF DIGITAL TECHNOLOGIES IN IMPROVING THE METHODOLOGICAL TRAINING OF FUTURE TEACHERS BASED ON THE “4K” MODEL (Universal International Scientific Journal, 2026)
This article analyzes the possibilities of using digital technologies in the development of methodological training of future teachers based on the “4K” model (creativity, critical thinking, communication and collaboration). The study considered the issues of developing teachers' professional competencies through modern pedagogical approaches, innovative methods and digital platforms. The results showed that digital technologies are an important factor in the effective formation of methodological training of future teachers.
Keywords: 4K model, methodological preparation, digital technologies, pedagogical competence, creative thinking, critical thinking.